A Validated High-Performance Liquid Chromatography-Tandem Mass Spectrometric (Lc-Ms/Ms) Method for Simultaneous Determination of R(+)-Ketorolac and S(−)-Ketorolac in Human Plasma and Its Application to a Bioequivalence Study. (18th October 2010) - Patri, Sabyasachi; Patni, Anil K.; Iyer, Sunil S.; Khuroo, Arshad H.; Monif, Tausif; Rana, Sachin; Kumar, Sudershan; Jain, Rakesh
Abstract : We report a selective, accurate, and reproducible liquid chromatography-tandem mass spectrometric (LC-MS/MS) method that employs solid phase extraction for quantification of ketorolac enantiomers in human plasma. Resolution of R(+)-ketorolac and S(−)-ketorolac was achieved using a Chiral-AGP column and a mobile phase of ammonium formate buffer (10 mM, pH4.70 ± 0.05 ):acetonitrile (85 : 15, v/v and 70 : 30, v/v) in a gradient time program. S(+)-etodolac was used as the internal standard (IS). Quantification was achieved using a positive electrospray ionization (ESI+) interface under multiple reaction monitoring (MRM) condition. The method was validated over the concentration range of 9.36–1198.69 ng/ml for R(+)-ketorolac and 6.07–776.74 ng/ml for S(−)-ketorolac. Matrix effect was found negligible and the method showed good performances in terms of accuracy (89.6–102.7%) and precision (1.7–6.7%) for both enantiomers. Extraction recoveries of R(+)-ketorolac, S(−)-ketorolac, and S(+)-etodolac were 82.04, 70.94, and 93.90%, respectively. Results of all stability exercises in human plasma were within acceptable limits. The method was successfully applied to a single dose cross over bioequivalence study in healthy human male volunteers. Incurred Sample Reanalysis (ISR) was performed by randomly selecting 10% of total subject samples of the study using Statistical Analysis Software (SAS). Values of 91.1% for R (+)-ketorolac and 83.5% for S(−)-ketorolac indicated good acceptance for ISR.